THE EFEECT OF USING MICROSOFT 365 APPLICATION ON STUDENTS SPEAKING SKILLS AT XII GRADE OF SMA NEGERI 2 PANGKALAN KERINCI - Ribka Aurelia Situmorang (Sean Institute, 2022)
This thesis focus on finding out the effect of using Microsoft 365 on students’ speaking skill at SMA Negeri 2 Pangkalan Kerinci. This study was conducted in experimental quantitative design. The population of this study was twelve grade of studenrs in SMA Negeri 2 Pangkalan Kerinci. The writer want to find different result test of asking and giving opinion in experimental class by apply Microsoft 365 technique with control class without using Microsoft 365. method There were fourty students of the twelve grade high school students as the sample of research. This study was conducted with two purposive sampling groups namely Experimental Class and Control Class. The experimental class was taught by using Microsoft 365, while control class was taught without Microsoft 365. The instrument of collecting the data was a speaking test. The writer took 20 students as experimental class. The data were taken by giving test . The test was used the pre-test and post-test for the both classes. The mean score of pre-test in Using Microsoft 365 is 46 and pre-test in convensional Learning is 33. The mean score post-test in using Microsoft 365 is 87,15 and post-test in convensional learning is 54. The data were analyzed by using t-test. The calculation shown that t-observed (3.44) was higher than t-table at the level of significance (α) 0.05 with the degree of freedom (df) 38. It means that there was a significant effect of Using Microsoft 365 technique on students speaking skill. So, the null hypothesis () is rejected and alternative hypothesis () is accepted. Keywords: Microsoft 365, Speaking skills, and Asking and Giving Opinion.